Towards a “branded” property developer: key traits for Malaysian housing market - Yap, Jeffrey Boon Hui; Tan, Chin Weng; Loo, Siaw Chuing; Lee, Wah Peng (Emerald, 2019)
Purpose: The purpose of this paper is to determine the significance of branding management by property developers in the Malaysian housing market and to examine the pivotal brand identity traits of property developers. Design/methodology/approach: An explanatory sequential mixed-methods research approach was adopted. The quantitative data from the questionnaire survey were subjected to descriptive statistics, and the ranking with category of significance of the hypothesised branding traits was determined using relative importance index technique. The findings were further validated through semi-structured interviews with five experienced industry practitioners. Findings: Results showed that the extremely significant (ES) branding identities are value for future investment and location, while the very significant (VS) traits are quality assurance, near to supporting infrastructure, reliability, professionalism, experience, warranties and technical ability. Industry experts affirmed the prospect of exploiting branding in enticing property buyers. Research limitations/implications: It is reasonable to infer that good branding positively stimulates buyer’s decision-making on purchasing residential property. This study attempts to discover the critical brand identity traits for property developers apt in the context of Malaysian housing market. Practical implications: Apart from the archetypal locational and financial factors, the findings suggested that top developers should emphasise innovative family-oriented design with an acceptable level of quality score for brand differentiation to further enhance the future value of their end products. Originality/value: The efficacy of brand management in the housing market has not yet been fully explored in research. This paper is expected to offer more profound insights into the strategic brand management towards “branded” property developers in the context of Malaysia and perhaps other countries with comparable backgrounds. © 2019, Emerald Publishing Limited.